Essential .NET, Volume 1 the Common Language Runtime - Box, Don; Sells, Chris (Addison-Wesley Professional, 2002)
"Don taught me stuff I didn't know about my own product! And I bet he'll teach you something, too."--The Foreword by James Miller, Lead Program Manager, Common Language Runtime, Microsoft Corporation Essential .NET, Volume 1, provides everything developers need to take full advantage of the power of Microsoft .NET. This book describes, in depth, the glue of the .NET Framework: the Common Language Runtime (CLR). Box and Sells explain the inner workings of the CLR-the rationale behind its design, the problems it solves, and the role of type in CLR programming-and show readers how to build better applications using the .NET Framework while gaining a more complete understanding of how the CLR works. The book is packed with the practical detail and expert advice only Don Box can provide. Topics covered include: CLR's evolution Assemblies in the .NET Framework The CLR type system Programming with type Objects and values Methods Explicit method invocation Application domains Security Interoperability Essential .NET, Volume 1, is an authoritative guide to the Microsoft .NET Common Language Runtime. Books in the Microsoft .NET Development Series are written and reviewed by the principal authorities and pioneering developers of the Microsoft .NET technologies, including the Microsoft .NET development team and DevelopMentor. Books in the Microsoft .NET Development Series focus on the design, architecture, and implementation of the Microsoft .NET initiative to empower developers and students everywhere with the knowledge they need to thrive in the Microsoft .NET revolution. 0201734117B10042002.
Keywords: Component software; Microsoft .NET Framework; Programming languages (Electronic computers); Composants logiciels